Development of a Graphic User Interface Focused on Multicriteria Analysis among a Plethora of Passive Exoskeletons to Improve the Social Inclusion of Infants in a Smart City - Restrepo Correa, Jorge Hernan (2019)
Passive exoskeletons are portable devices that have beneficial functions that can address ergonomic needs taking advantage over other technological supports. They were developed to multiply human power. Passive exoskeletons have been introduced in some industrial environments, but there has been relatively little research that has examined the possible benefits, drawbacks, and tradeoffs of using the exoskeleton in a workplace. These exoskeletons require different approaches towards compliance with requirements such as use, acceptability in the workplace and possible security problems among others. Consequently, the present investigation has planned to evaluate different passive exoskeletons based on criteria such as: cost, multitasking, performance, physical demand, and influence of the mass of the tool. The criteria will be modeled and evaluated with the AHP methodology (Analytical Hierarchy Process), in order to support the acquisition decision, in the present investigation a multicriteria analysis is carried out that will allow identifying which would be the best exoskeleton of its type and how it would help children with some type of motor defect in a Smart City with regard to their social inclusion.